Transcript Profiling of Different Arabidopsis thaliana Ecotypes in Response to Tobacco etch potyvirus Infection - Hillung, Julia; Cuevas, José M.; Elena, Santiago F. (Frontiers in Microbiology, 2012)
The use of high-throughput transcript profiling techniques has opened the possibility of identifying, in a single experiment, multiple putative viral targets on infected host. Several studies have used this approach to analyze the response of Arabidopsis thaliana to the infection of different RNA and DNA viruses. However, the possible differences in response of genetically heterogeneous ecotypes of the plant to the same virus have never been addressed before. Here we have used a strain of Tobacco etch potyvirus (TEV) experimentally adapted to A. thaliana ecotype Ler-0 and a set of seven plant ecotypes to tackle this question. Each ecotype was inoculated with the same amount of the virus and the outcome of infection characterized phenotypically (i.e., virus infectivity and accumulation and symptoms development). Using commercial microarrays containing probes for more than 43000 plant transcripts, we explored the effect of viral infection in the plant transcriptome. In general, we found that ecotypes differ in the way they perceive and respond to the virus. While some showed strong symptoms and accumulated large amounts of viral genomes, others only developed mild symptoms and accumulated fewer viruses. At the transcriptomic level, ecotypes could be classified into two groups according to the particular genes whose expression was altered upon infection. Moreover, a functional enrichment analyses showed that the two groups differed in the nature of the altered biological processes. While the group constituted by ecotypes developing milder symptoms and allowing for lower virus accumulation tend to over-express genes involved in abiotic stresses and in the construction of new tissues, those ecotypes for which infection was severer and allowed for more viral accumulation, defense genes tend to be over-expressed, deviating the necessary resources from building new tissues.